Reconfigurable Orbital Electrowetting for Controllable Droplet Transport on Slippery Surfaces - Jiayao Wu; Huafei Li; Yifan Zhou; Ge Gao; Teng Zhou; Ziyu Wang; Huai Zheng (Micromachines)
The controllable transport of droplets on solid surfaces is crucial for many applications, from water harvesting to bio-analysis. Herein, we propose a novel droplet transport controlling method, reconfigurable orbital electrowetting (ROEW) on inclined slippery liquid-infused porous surfaces (SLIPS), which enables controllable transport and dynamic handling of droplets by non-contact reconfiguration of orbital electrodes. The flexible reconfigurability is attributed to the non-contact wettability modulation and reversibly deformable flexible electrodes. ROEW graphically customizes stable wettability pathways by real-time and non-contact printing of charge-orbit patterns on SLIPS to support the continuous transport of droplets. Benefiting from the fast erase-writability of charges and the movability of non-contact electrodes, ROEW enables reconfiguration of the wetting pathways by designing electrode shapes and dynamically switching electrode configurations, achieving controllable transport of various pathways and dynamic handling of droplet sorting and mixing. ROEW provides a new approach for reconfigurable, electrode-free arrays and reusable microfluidics.